Electronic structure of K-doped picene film on HOPG. (21st December 2016) - Wakita, T; Okazaki, H; Jabuchi, T; Hamada, H; Muraoka, Y; Yokoya, T
Abstract: We have performed potassium (K)-doping dependent photoemission (PES) measurements of picene film on highly oriented pyrolytic graphite (HOPG). K-doping dependent valence band PES data exhibits a shift of the valence band to a higher binding energy, indicative of the charge transfer from the K atoms to the picene film. K-doping dependent PES spectra near the Fermi level ( E F ) show the appearance and disappearance of a Fermi edge, indicating the metallic properties of the film at certain K concentrations. High-resolution PES spectrum at the lowest measured temperature does not show an opening of the superconducting gap, requesting further studies to explore the superconducting properties of the K-doped picene film. The results will be discussed by comparison with previous and recent spectroscopic studies.